Gerakan SEHATI: Memberdayakan Warga Desa Setro dalam Mengenal Faktor Risiko dan Mencegah Komplikasi Nyeri Muskuloskeletal - Kusumah, Irwin Prijatna; Effendy, Lyndia; Arisanti, Raden Roro Shinta; Alim, Denys Putra; Thang, Belinda Wijaya; Susanto, Vivian Rosiana (Universitas Nusantara PGRI Kediri, 2025)
Musculoskeletal pain such as aches and pains is a health problem that is closely related to a sedentary lifestyle and an unbalanced diet. This study aims to analyze risk factors and provide educational recommendations based on questionnaire data from 38 respondents in Setro Village, Menganti, Gresik Regency, East Java. Descriptive methods were used to evaluate health parameters (age, BMI, blood pressure, uric acid levels, cholesterol), sitting habits, screen time, physical activity, and consumption of sweet foods/drinks. The results showed that the majority of female respondents (93%) were aged 40-68 years with a high prevalence of risk factors: 60% overweight, 10% obesity (BMI>25), 16% hypertension, and extreme uric acid/cholesterol levels (up to 11.8 mg/dL and 339 mg/dL). As many as 73% reported musculoskeletal complaints (joint pain, tingling) that correlated with long sitting habits (>4 hours/day), lack of exercise (40% never did physical activity), and daily consumption of sweet drinks (60%). The results of this study indicate that a structured educational intervention is needed to increase awareness of low-purine diets, regular physical activity (eg, elderly gymnastics/jogging), and sedentary screen time management. The conclusion of the study emphasizes the importance of multidisciplinary collaboration (medical personnel, government, community) in a healthy lifestyle and healthy diet-based prevention program to prevent musculoskeletal complications.